A C1qDC Protein (HcC1qDC6) with Three Tandem C1q Domains Is Involved in Immune Response of Triangle-Shell Pearl Mussel (Hyriopsis cumingii) - Huang, Ying; Wu, Lei; Jin, Min; Hui, Kaimin; Ren, Qian (Frontiers in Physiology, 2017)
C1q-domain-containing (C1qDC) proteins are a family of proteins with a globular C1q (gC1q) domain and participate in several immune responses. In this study, a C1qDC gene was identified from the triangle-shell pearl mussel Hyriopsis cumingii (designated as HcC1qDC6). This gene has a full-length cDNA of 1782 bp and an open reading frame of 1335 bp that encodes a 444-amino acid polypeptide containing three gC1q domains. HcC1qDC6 contains at least five exons and four introns. The mRNA transcripts of HcC1qDC6 were found to have the highest expression levels in the mantle tissue. The expression levels in the mantle and hepatopancreas were significantly upregulated by Staphylococcus aureus and Vibrio parahaemolyticus challenges. Moreover, knockdown of HcC1qDC6 inhibits the expression of two immune-related genes (tumor necrosis factor and whey acidic protein). The recombinant proteins of C1q1, C1q2 and C1q3 all exhibit a binding activity against seven bacterial species and directly bind to peptidoglycan and lipopolysaccharide. The results indicate that HcC1qDC6 is involved in the innate immunity of H. cumingii.